2021
DOI: 10.1159/000516519
|View full text |Cite
|
Sign up to set email alerts
|

Routine Use of Air Tamponade in Pars Plana Vitrectomy for Primary Rhegmatogenous Retinal Detachment Repair

Abstract: <b><i>Purpose:</i></b> The aim of this study is to establish if air can be considered as a safe substitute for long-lasting tamponade agents for primary rhegmatogenous retinal detachment (RRD) treatment, regardless of the position or the number of retinal breaks. <b><i>Methods:</i></b> In this study, 230 consecutive patients (236 eyes) who underwent a pars plana vitrectomy (PPV) for primary RRD with air or SF<sub>6</sub> tamponade from January 2014 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Different surgeons performing the procedures within the studies were also observed in the included studies [19]. Besides, two included studies [10, 23] did not compare the baseline characteristics between the air and gas groups; thus, potential selection bias between the two groups cannot be ruled out. In the overall bias analysis, five observational studies [11, 18, 19, 22] were rated as having a moderate risk of bias, one observational study [20] with a serious risk of bias, and three observational studies [10, 21, 23] with a critical risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Different surgeons performing the procedures within the studies were also observed in the included studies [19]. Besides, two included studies [10, 23] did not compare the baseline characteristics between the air and gas groups; thus, potential selection bias between the two groups cannot be ruled out. In the overall bias analysis, five observational studies [11, 18, 19, 22] were rated as having a moderate risk of bias, one observational study [20] with a serious risk of bias, and three observational studies [10, 21, 23] with a critical risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, two included studies [10, 23] did not compare the baseline characteristics between the air and gas groups; thus, potential selection bias between the two groups cannot be ruled out. In the overall bias analysis, five observational studies [11, 18, 19, 22] were rated as having a moderate risk of bias, one observational study [20] with a serious risk of bias, and three observational studies [10, 21, 23] with a critical risk of bias. The detailed risk of bias assessment of the included studies is shown in online supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative characteristics were almost similar between the two groups. They reported that PPV with air tamponade was effective for RRD regardless of the location of the retinal breaks 13 . The present study prospectively evaluated the primary success rate based on the location of retinal breaks (i.e., upper and lower breaks).…”
Section: Discussionmentioning
confidence: 99%